The Cyclooxygenase-2 and Nuclear Factor-kappa B Expressions in Colorectal Polyps - Ahmar Abyadh; Diah Rini Handjari; Murdani Abdullah; Pamela Abineno Damaledo; Abdul Aziz Rani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Background: Cyclooxygenase-2 (COX-2) is the rate-limiting enzyme in prostaglandin synthesis, while nuclear factor kappa B (NF-kB) is a family of transcription factors. Both play an important role in tumorigenesis. In the present study, we examined NF-kB and COX-2 expressions pattern, and their association in neoplastic and non-neoplastic colorectal polyps (CP). Method: Formalin-fixed and paraffin embedded tissue blocks from 77 patients with CP were immunostained with anti-NF-kB (p 65) and anti-COX-2. Expressions of NF-kB, and COX-2 were detected immunohistochemically. The relationship between these expressions and the two types of CP, and other clinicopathological findings were evaluated Results: The expressions of NF-kB and COX-2 in patients with neoplastic and non-neoplastic CP were high. The results of this study indicated that generally in CP, NF-kB was associated with COX-2 and the association was also seen in neoplastic and non-neoplastic polyps. There was no significant difference of NF-kB and COX-2 expressions in terms of patient’s age, sex, histologic type, and location of the CP. Neoplastic CPs were more common in the distal colon, female patients and older patients ( 60 years) compared with non-neoplastic CPs. Neoplastic CP were located more at the distal colon, more in female, and more in older ( 60 years) patients as compared with the non-neoplastic CP. Further studies are needed to elaborate the role of inflammation in sporadic colorectal carcinogenesis. Conclusion: The expressions of NF-kB and COX-2 in patients with CP were high, and strong correlated each other. There were no significant differences between expression of NF-kB and COX-2 in neoplastic and non-neoplastic polyps. Keywords: colorectal polyps (CP), NF- B, COX-2, inflammation